Sustained Intermittent Hypoxemia Induces Adiponectin Oligomers Redistribution and a Tissue-Specific Modulation of Adiponectin Receptor in Mice - Pierard, Mélany; Tassin, Alexandra; Conotte, Stéphanie; Zouaoui Boudjeltia, Karim; Legrand, Alexandre (Frontiers in Physiology, 2019)
Introduction: Hypoxaemia is a critical component of several respiratory diseases and is known to be involved in the processes underlying co-morbidities associated to such disorders, notably at the cardiovascular level. Circulating level of Adiponectin (Ad), known as a metabolic regulator and cardio-protective hormone was previously suggested to be reduced by hypoxia but consequences of such variation are unclear. The evaluation of the specific effect of hypoxaemia on Ad forms and receptors could improve the understanding of the involvement of Ad axis in hypoxaemia-related diseases. Methods: Ad-pathway components were investigated in a murine model of sustained intermittent hypoxaemia (FiO2 10%, 8h/day, 35 days). Results: Sustained intermittent hypoxaemia induced a redistribution of Ad multimer in favour of HMW forms, without change in total plasmatic level. Mice submitted to hypoxia also exhibited tissue-specific modification of adiporeceptor (AdipoR) protein level without mRNA expression change. A decreased AdipoR2 abundance was observed in skeletal muscle and heart whereas AdipoR1 level was only reduced in muscle. No change was observed in liver regarding AdipoR. Lipid profile was unchanged but glucose tolerance increased in hypoxemic mice. Conclusion: Sustained intermittent hypoxaemia, per se, modify Ad oligomerisation state as well as AdipoR protein abundance in a tissue-specific way. That suggest alterations in Ad-dependant pathways in pathological conditions associated to sustained intermittent hypoxaemia. Investigation of Ad-pathway components could therefore constitute useful complementary criteria for the clustering of patients with hypoxaemia-related disease and management of co-morbidities, as well as to develop new therapeutic strategies.